PENGUKURAN DAN PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN DI HOTEL XYZ PONTIANAK - WIRADINATA, GUNTARA (Jurnal TIN Universitas Tanjungpura, 2017)
Hotel XYZ Pontianak require that employees provide the best service to the customers because the employee must have excellent stamina. If the absence of employees increased, decreased work motivation and high labor indiscipline can be concluded that an employment boredom experienced by those employees. The purpose of this research is to improve the productivity performance of employees and find out how much impact the performance of employees to work productivity views of the absent employee, motivation, discipline kerjadan hours at Hotel XYZ Pontianak.This study uses the calculation of labor productivity. Procedures for implementing the productivity was observed for a period of work activity are taken irregularly (the observation time is determined by the researcher) and record whether employees are in a state of working or not working. It should be considered in measuring dimension - the dimension of working hours and absenteeism Absenteeism very positive effect on work productivity due to employees who were not present and would pose a burden for employees in lieu.The results of this study indicate that attendance and working hours have a positive effect on work productivity. Based on employee attendance data in 2016 had the highest value, the total absence of its largest year before. Productivity is the lowest value in March has a value that is 95.69%, while the value of the highest productivity in January has a value that is 98.88% recap of absenteeism began January 2016 - March 2016 states that three days or 72 hours of work were lost in last three months. Lost work hours or workload should be replaced by another employee, resulting workload add or substitute employees working hours and hours of work.Keywords : productivity, working hours, absenteeism, hotel, employee performance